KATEGORI FATIS BAHASA BANJAR HULU KABUPATEN INDRAGIRI HILIR - Rapikawati, Rapikawati; Charlina, Charlina; Hakim, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The study aims to describe the form of phatic communication in the Language of Banjar Hulu Indragiri Hilir Regency. This research was qualitative research used descriptive methods. This research was conducted in Indragiri Hilir Regency. The time needed in research uses phatic categories in society. The instrument used in this study were found, obtained and obtained their own data, by using interviews, conversations or discussions, and equipped with supporting tools such as recording equipment, and small notebooks. This study used data collection techniques, namely tapping conversational techniques. The results of the research were as follows; (1) As for the fat form it is divided into 9 particle forms and 2 phytic forms. Forms of particles (bah, jen, kah, leh, nah, nang, pang, ah, am), phatic word categories (ai and bah). (2) the phatic functionsinclude in the Upper Banjar Language state affirmation, rule, question, affirmation, designation.Keywords: Phatic Category, Banjar Hulu language.